Legal Analysis of the Implications of the ASEAN Agreement on E-Commerce for Electronic Business Contracts in Indonesia - Wilbert, Wilbert; Siregar , Mahmul; Sukarja, Detania; Natcha, Natcha (Jurnal Suara Hukum, 2024)
The Industrial Revolution 4.0 (4IR) has ushered in significant transformations, notably the rise of electronic commerce (e-commerce), which transcends national borders and presents challenges related to state sovereignty, legal certainty, security, and the formation of contracts. To address these complexities, the ASEAN Agreement on E-Commerce aims to facilitate e-commerce across ASEAN countries. Indonesia, as an ASEAN member, has ratified this agreement into national law, impacting various aspects, notably the regulation of digital business contracts. This study seeks to explore these implications through qualitative analysis of secondary data, employing normative legal methodologies and a legal approach. The ASEAN Agreement on E-Commerce introduces additional regulations that establish norms for individuals engaging in cross-border electronic transactions within ASEAN. This framework is crucial for harmonizing legal standards and fostering a conducive environment for international business activities within the ASEAN region.